Elevated serum procalcitonin levels in patients with melioidosis. - Smith, MD; Suputtamongkol, Y; Chaowagul, W; Assicot, M; Bohuon, C; Petitjean, S; White, N (1995)
The prognostic value of serum procalcitonin levels in 43 patients with acute melioidosis, an infection with a wide range of clinical manifestations, was assessed. In eight patients with mild localized infections, the median procalcitonin levels were 0.13 ng/mL (range, 0.02-0.46 ng/mL), which were similar to those in 19 healthy controls (median, 0.07 ng/mL; range, 0.03-0.15 ng/mL). In the patients with severe infections, the initial procalcitonin levels were significantly higher in the patients who died (median, 350 ng/mL; range, 63-3,538 ng/mL) than in the survivors (median, 19 ng/mL; range, 0.55-387 ng/mL) (P < .0001); 16 of 19 patients with procalcitonin levels of > 100 ng/mL died, compared with 2 of 16 patients with levels of < 100 ng/mL (relative risk, 6.7; 95% confidence interval, 1.8-25; P = .0001). In those patients who survived, the subsequent procalcitonin levels reflected closely the clinical course of their infection. The serum concentration of procalcitonin correlates well with the severity of Pseudomonas pseudomallei infection and is comparable with other acute-phase markers. However, this prognostic indicator and marker of continuing disease activity is not specific to melioidosis and could be applied to other severe infections.